Ten Things Evaluation Needs: An Evaluation Needs Assessment - James R. Sanders (The Evaluation Center at Western Michigan University, 2006)
It is important to take stock, to do a rolling needs assessment, every year or so to guide the development of evaluation as a profession. What are the unknowns that continue to plague us? By identifying issues and problems in evaluation for which we have no good answers, we can direct our research energies in productive ways. Said another way, here are ten dissertation topics just waiting to be claimed.